Just another Chinese Christian? - TSE, Justin Kh (Institutional Knowledge at Singapore Management University, 2012)
At a lunch reception for a religious event, I got hit with a double whammy: Where was I really from? And did I know anything about Ming vases? Or perhaps my religion is the problem. I happen to be a Christian of Chinese ethnicity who studies Chinese Christians.